Involvement, topics, and roles of nurses in shared decision‐making with patients with dementia in acute hospitals: An integrative review - Annette Keuning‐Plantinga; Josephine Stoffels; Petrie F. Roodbol; Evelyn J. Finnema; Barbara C. Van Munster (Wiley, 2023)
Abstract Aim To describe nurses' roles, involvement, and topics in shared decision‐making with older patients with dementia in acute hospitals. Design An integrative review. Methods A systematic search was performed until April 2022 in PubMed, PsychInfo, CINAHL, and Cochrane, followed by a manual search on the reference lists of relevant systematic reviews. Studies were independently screened, appraised using the Joanna Briggs Institute (JBI) methodology, and extracted by two reviewers. Results Nine studies were included. Nurses were involved as treatment team members, intermediates, or patient supporters. Nurses' roles were most explicit in the preparatory phase of shared decision‐making. The step of 'developing tailor‐made options' was limitedly identified. 'Deliberating and trying options to reach a decision' were described from an outsider's perspective in which nurses attempted to influence the decision. In conclusion, nurses primarily have a role in decision‐making by supplementing patient information. Patient and Public Contribution No Patient or Public Contribution.